1976
DOI: 10.1136/jnnp.39.3.283
|View full text |Cite
|
Sign up to set email alerts
|

Acute optic neuritis and the prognosis for multiple sclerosis.

Abstract: SYNOPSIS In a retrospective survey of acute optic neuritis 144 cases in adults were found and, of these, 127 were reviewed, five had died of causes related to multiple sclerosis, and 12 were lost to follow-up. There was a statistically significant seasonal variation in the incidence of optic neuritis. When the life-table method of analysis was used, the probability of developing multiple sclerosis rises to 78% 15 years after an episode of optic neuritis. At review, 49 (730 %) of the 67 patients with multiple s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
30
0
7

Year Published

1979
1979
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(43 citation statements)
references
References 17 publications
6
30
0
7
Order By: Relevance
“…18 Several natural history studies have suggested that optic neuritis at CIS onset may signify a form of MS with a better prognosis compared with other syndromes. [24][25][26] However, among patients with abnormal cranial MRI studies and monosymptomatic presentation at CIS onset, syndrome type appears to have little effect on disease course. 17 Serial MRI activity also has been explored as a predictor of long-term disability.…”
Section: Results From Phase 3 Studies Of Ifnβ In Patients With a Cismentioning
confidence: 99%
“…18 Several natural history studies have suggested that optic neuritis at CIS onset may signify a form of MS with a better prognosis compared with other syndromes. [24][25][26] However, among patients with abnormal cranial MRI studies and monosymptomatic presentation at CIS onset, syndrome type appears to have little effect on disease course. 17 Serial MRI activity also has been explored as a predictor of long-term disability.…”
Section: Results From Phase 3 Studies Of Ifnβ In Patients With a Cismentioning
confidence: 99%
“…Comparison of the present series of ON with American [3,4,6], European [1,2,5,7,8], and Japanese studies [9] revealed no sub stantial differences in the clinical features of ON (maleifemale ratio, age at onset, later ality, fundus appearance, level of visual im pairment, final visual acuity, visual field de fect, and recurrences).…”
Section: Discussionmentioning
confidence: 98%
“…In one study, the 10-year risk of developing MS after an initial episode of ON was 56% if patients had one or more typical lesions on the baseline magnetic resonance imaging (MRI) scan of their brain, those with no lesions having a 22% risk [4]. Life-table analyses have shown that up to 78% of all ON patients progress to clinically definite MS within 15 years of follow-up [15]. Moreover, white matter abnormalities typical for MS are found on MRI in 48-62% of patients with monosymptomatic ON [3,12,18], and MS patients have shown lesions in the optic nerves in up to 94-99% of autopsy cases [16,26].…”
Section: Introductionmentioning
confidence: 99%